"Gymnasts Are Like Wine, They Get Better With Age": Becoming and Developing Adult Women's Artistic Gymnasts. Issue 3 (3rd July 2017) - Barker-Ruchti, Natalie; Kerr, Roslyn; Schubring, Astrid; Cervin, Georgia; Nunomura, Myrian
ABSTRACT: Women's artistic gymnastics is commonly understood to require early entrance and intense training during childhood. Most gymnasts retire before reaching adulthood. In recent years, the gymnast population at the highest level has "aged." In this article, we adopt a socio-pedagogical perspective to explore the training contexts, pubertal development, and associated learning 10 older elite gymnasts reported. We develop a cultural perspective of gymnast development and show that transitioning through puberty allowed the gymnasts to extend their careers. Support from their coaches and parents, self-reflective time, and genetic predispositions facilitated the transitioning. Through this, gymnasts gained control over self, body, relationships, and performance. In conclusion, we provide implications for gymnast development practice.